Effect of Transient Creep on the Structural Performance of Reinforced Concrete Walls under Fire - Jun Chen (Buildings, 2024)
This paper investigates and reveals the effect of the high-temperature transient creep on the structural performance of RC walls under fire. A theoretical model is established, which explicitly includes the transient creep and accounts for the explosive spalling, the material, and geometric nonlinearities under fire. The effects of the transient creep on the structural response and fire resistance of RC walls with little spalling and with explosive spalling are investigated, respectively, with elucidation of the mechanisms. The influences of wall geometries, concrete properties, and the eccentricity of load on the effect of the transient creep are quantitatively studied. Finally, the results are validated through comparison with tests in the literature. It is revealed that the transient creep significantly reduces the fire resistance of RC walls with little spalling by up to and greater than 60%, by decreasing the deflection toward the heated side. However, it increases the fire resistance of RC walls with explosive spalling by up to about 40% by reducing the spalling extent due to the stress relaxation effect. The stress relaxation effect of the transient creep has a crucial role in determining the spalling manner. The load level, the eccentricity of load, and the wall geometries are key influencing factors which have contrary influences on the effect of the transient creep on the fire resistance of RC walls with little spalling and with explosive spalling.